Lipid assessment, cholesterol and fatty acid profile of meat from broilers raised in four different rearing systems - Giampietro-Ganeco, Aline [UNESP]; Boiago, Marcel M.; Mello, Juliana L. M.; DE SOUZA, Rodrigo A. [UNESP]; Ferrari, Fábio B. [UNESP]; DE SOUZA, Pedro A. [UNESP]; Borba, Hirasilva [UNESP] (FapUNIFESP (SciELO), 2020)
Evaluated lipid and cholesterol concentration and fatty acid profile of raw breast, thigh and drumstick meat from broilers raised in different rearing systems. Were used 200 male broiler carcasses from four different rearing systems (n=50 from conventional intensive; n=50 from organic; n=50 from free-range; and n=50 from antibiotic-free) distributed in a completely randomized design with four rearing systems and 50 replications (carcasses). Breast meat from conventional broilers showed higher lipid (1.47) and cholesterol (34.13) concentration. Thigh and drumstick meat from free-range broilers had higher lipid (7.53/4.73) and cholesterol (45.55/53.65) concentration. Fat contained in breast, thigh and drumstick meat from free-range broilers showed higher levels of polyunsaturated fatty acids. Fat from breast and thigh meat from free-range broilers showed higher total concentration of ω3 and ω6 fatty acids. Fat from thigh meat from organic broilers showed higher levels of EPA (C20:5n3) and DHA (C22:6n3). Fat from drumstick meat from free-range broilers showed higher total concentration of ω3 and ω6 fatty acids. Meat from chickens raised in alternative rearing systems offers less risk to cardiovascular health because it presents lower concentrations of lipids and cholesterol, greater amounts of polyunsaturated fatty acids, which are beneficial for human health.
Keywords: Breast; Drumstick; Free-range; Organic; Thigh